2019
DOI: 10.3390/ijerph16030489
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Physical Activity is Associated with Sexual Activity in Older English Adults

Abstract: Physical activity (PA) is a potential modifiable correlate of the age-related decline in sexual function, but no studies have explicitly tested this. This study aimed to examine associations between PA, television viewing (TV) time and sexual activity, problems, and concerns. Data were from 7,038 men and women aged ≥50 years participating in the English Longitudinal Study of Ageing. PA and TV viewing time were self-reported. Sexual behaviour and concerns were assessed by self-completion questionnaire. Covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…A sedentary lifestyle is well known to be associated with adverse physical health outcomes, but also with worsened psychological health [36] including diminished sexual activity and greater sexual problems. Conversely, promoting physical activity among older adults can improve sexual activity [13]. In our review, PFM training was the most commonly used set of exercises (in six studies, five of which were RCTs).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A sedentary lifestyle is well known to be associated with adverse physical health outcomes, but also with worsened psychological health [36] including diminished sexual activity and greater sexual problems. Conversely, promoting physical activity among older adults can improve sexual activity [13]. In our review, PFM training was the most commonly used set of exercises (in six studies, five of which were RCTs).…”
Section: Discussionmentioning
confidence: 96%
“…However, little attention has been paid in the literature to the possible links between physical exercise and sexual function. The practice of physical exercise can be a key factor in preventing women's sexual problems [13], given that many of the physiological mechanisms involved in exercise also play a part in female sexual function [14]. To our knowledge, a few systematic reviews studying the effects of physical exercise on female sexual function have been published, but only pelvic floor muscle (PFM) exercises were analyzed, and they were not conducted in postmenopausal women [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Romantic expression in aging depends largely on how romantic and sexual expression happened throughout life (DeLamater, 2012). This expression implies a positive perspective of aging and is hindered by factors such as low sexual self-concept, loss of a partner and negative sexual experiences (DeLamater & Moorman, 2007;Smith et al, 2019). The social perception of older adults as passive agents-without sexuality, libido and romanticism to develop an affective-sexual relationship-removes power and social autonomy from sexual expression (DeLamater, 2012;Traeen, et al, 2017aTraeen, et al, , 2017b.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one large study among adults found that men who spent between 2 and 4 h a day sedentary had significantly higher odds of reporting any sexual activity (OR = 1.61, 95% CI: 1.08-2.41), thinking about sex frequently (OR = 1.75, 95% CI: 1.16-2.63) and frequent sexual intercourse (OR = 1.44, 95% CI: 1.08-1.93) than those who spent less than <2 h a day (13). Furthermore, higher levels of moderate or vigorous physical activity have been shown to be associated with higher levels of sexual activity among adults (13). However, to date, the association between sedentary behavior and sexual behavior has not been investigated among adolescents, while the influential factors in this association are largely unknown.…”
Section: Introductionmentioning
confidence: 96%